2003
DOI: 10.1017/s0031182003003056
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of the tapeworm Raillietina trapezoides infection in the fat sand rat Psammomys obesus in Tunisia: season, climatic conditions, host age and crowding effects

Abstract: The tapeworm Raillietina trapezoides was studied in a Tunisian population of the fat sand rat Psammomys obesus. Seasonal changes in the abundance of parasite and host were monitored in a longitudinal field survey lasting 20 months. In total 582 intestinal samples were collected during 10 trapping sessions between May 1995 and January 1997 and examined. The impact of abiotic and biotic factors on the prevalence and parasite burden were explored, using generalized linear models. R. trapezoides showed a seasonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…Raillietina species have been reported as parasites of Meriones spp. as well as of other gerbillin and Dipodidae rodents: Gerbillus spp., Psammomys obesus (Fichet-Calvet et al 2003) and Jaculus jaculus (Wertheim et al 1986;Ben Faleh et al 2012); here we report two Meriones species as definitive hosts for this helminth.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Raillietina species have been reported as parasites of Meriones spp. as well as of other gerbillin and Dipodidae rodents: Gerbillus spp., Psammomys obesus (Fichet-Calvet et al 2003) and Jaculus jaculus (Wertheim et al 1986;Ben Faleh et al 2012); here we report two Meriones species as definitive hosts for this helminth.…”
Section: Discussionsupporting
confidence: 61%
“…Some studies (e.g. Fichet-Calvet 2003;Ben Faleh et al 2012) consider that the Raillietina species parasites of rodents is R. trapezoïdes for which the number of egg cells in each capsule is known to be around 25; however, Raillietina specimens found in the current study showed different numbers of cells. This result requires further taxonomic study of these specimens to determine their parasitic entities.…”
Section: Discussioncontrasting
confidence: 49%
“…There are various examples of either increases (see Fichet-Calvet et al 2003 and references therein), decreases (Henricson 1977;Quinnell 1992;Davies and Gavgani 1999;Knudsen et al 2002) or Wrst an increase and then a decrease (convex age-infestation curve; Gregory et al 1992;Sorci 1996) in infestation level with host age. The shape of the relationship between host age and parasite infestation seems to depend on both host and parasite taxa (Wilson et al 2002;Hawlena et al 2005 and references therein), but it is usually consistent within a parasite-host association.…”
Section: Introductionmentioning
confidence: 99%
“…environmental stress) [37] and may also differ between males and females (due to faster aging of men) [38]. Secondly, differential parasite abundance in hosts belonging to different age cohorts has been reported for various host and parasite taxa [3941]. However, the influence of host age on the distribution pattern of parasite abundance differs among different host-parasite associations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of host age on the distribution pattern of parasite abundance differs among different host-parasite associations. In some host-parasite associations, the abundance of parasites increases with the age of the host [39], while in other associations it increases or decreases in the youngest and oldest hosts compared to hosts of median age (called “adult hosts”)[40]. In fact, acquired resistance against parasites may be lower in young or old hosts than in median-age hosts.…”
Section: Discussionmentioning
confidence: 99%